English medium instruction: Global views and countries in focus: Introduction to the symposium held at the Department of Education, University of Oxford on Wednesday 4 November 2015. (18th January 2017) - Macaro, Ernesto; Hultgren, Anna Kristina; Kirkpatrick, Andy; Lasagabaster, David
Abstract : In virtually every research paper on this topic we come across we read that, in the particular context that the writer is operating, English as a medium of instruction (EMI) is on the increase. But what exactly is EMI? If we consider every classroom around the world in which learners are exposed to English language as their second language (L2) we are faced with a huge variety: English as a foreign language (EFL); Immersion, English for academic purposes; English for specific purposes, English for examination purposes, Content and language integrated learning (CLIL); content-based teaching; content-based language teaching, and so on. And then we have EMI. Here at the EMI Oxford Centre we define EMI as: The use of the English language to teach academic subjects (other than English itself) in countries or jurisdictions in which the majority of the population's first language is not English. This definition was first used in Dearden (2015).